2018
DOI: 10.18203/2349-3933.ijam20183459
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Vit B12 levels with metformin usage among type 2 diabetic patients in a tertiary care hospital

Abstract: Background: T2DM is a metabolic disorder that is increasingly becoming a public health concern. The disease is associated with a variety of systemic macrovascular and microvascular complications. Diabetic peripheral neuropathy (DPN) is the most common complication, and it may eventually develop in up to 50% of patients. It is assumed that prolonged use of metformin causes vitamin B12 deficiency. The clinical presentation of vitamin B12 deficiency generally includes haematological and neurological manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…American Diabetes Association 2019 recommended Metformin for the treatment of type 2 DM and should be continued as long as it is tolerated 3 . Nareddy et al reported that metformin can cause cobalamin deficiency 4 . Cobalamin is associated with various metabolic functions, including red cell generation and intact nervous system, and so its dysfunction can cause anemia and neurological impairment 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…American Diabetes Association 2019 recommended Metformin for the treatment of type 2 DM and should be continued as long as it is tolerated 3 . Nareddy et al reported that metformin can cause cobalamin deficiency 4 . Cobalamin is associated with various metabolic functions, including red cell generation and intact nervous system, and so its dysfunction can cause anemia and neurological impairment 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Authors observations do not support the findings and recommendation of one of the studies from India which reported that the diabetic patients on metformin were not having any vitamin B12 deficiency and that the supplementation of vitamin B12 in long term metformin treatment was not necessary and reduced the financial burden. 22…”
Section: Discussionmentioning
confidence: 99%
“…21 A study from India reported negative correlation between metformin use and vitamin B12 levels and that the supplementation of vitamin B12 was not necessary and reduced the financial burden. 22 Therefore, we are more interested and aim to further correlate metformin use in treatment of T2DM and vitamin B12 levels through this study in Sub-Himalayan region of north India.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous observational studies [9,10] and case reports [11][12][13] have reported an elevation in the prevalence of vit. B12 insufficiency in patients with type 2 diabetes mellitus (T2DM), especially with the chronic use of metformin [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…B12 levels by 22% versus placebo and 29% versus glyburide. Several consequent crosssectional studies [9,10], case reports [11,13], and randomized controlled trials [14,15] have demonstrated the downsides of metformin too.…”
Section: Introductionmentioning
confidence: 99%